คำปรากฏร่วมจำเพาะในเค้าโครงปริญญานิพนธ์ของครูสอนภาษาอังกฤษ ในฐานะภาษาต่างประเทศ - สมคะเน, ชยุตินิตย์; จันทร์เสม, อัญชลี; สุขเสรีทรัพย์, นิตยา (บรรณศาสตร์ มศว, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีจุดประสงค์เพื่อวิเคราะห์ความรู้ในการใช้คำปรากฏร่วมจำเพาะของนักศึกษาปริญญาโทจำนวน 15 คนในสาขาวิชาการสอนภาษาอังกฤษเป็นภาษาต่างประเทศ ช่วงปีการศึกษา 2554-2557 โดยรวบรวมข้อมูลจากงานเขียนเค้าโครงปริญญานิพนธ์ฉบับต้นร่างในหัวข้อภูมิหลัง เพื่อศึกษาประเภทของข้อผิดพลาด ความถี่ของข้อผิดพลาด และสาเหตุของข้อผิดพลาด ผลการวิจัยพบว่า ข้อผิดพลาดจากการใช้คำปรากฏร่วมจำเพาะทางด้านคำศัพท์ถูกพบมากกว่าด้านไวยากรณ์ ผลการวิจัยยังพบว่า ข้อผิดพลาดจากการใช้คำปรากฏร่วมจำเพาะทางด้านคำศัพท์ ถูกพบมากในชนิดของการใช้คำกริยาที่ตามด้วยคำนาม ในส่วนของข้อผิดพลาดจากการการใช้คำปรากฏร่วมจำเพาะทางด้านไวยากรณ์ ถูกพบมากในชนิดของการใช้คำนามที่ตามด้วยคำบุพบทและการใช้คำกริยาที่ตามด้วยบุพบทและกรรม ส่วนสาเหตุของหลักที่ทำให้เกิดข้อผิดพลาดมาจากอิทธิพลของภาษาแม่เป็นส่วนใหญ่ Abstract This research study is aimed at analyzing collocation knowledge of teachers who teachEnglish as a foreign language. The participants of this study are 15 Thai graduate students inTeaching English as a Foreign Language (TEFL) program, academic year 2011-2014. The datais collected from the first draft of participants’ research proposals in the part of backgroundof the study. Types and frequency of English collocational errors are investigated and thesources of errors are discussed. The results of the study show that the participants mademore lexical collocational errors than grammatical ones. Among the lexical collocational errors,it is revealed that the participants make errors on verbs that are followed by a noun the most.However, the study shows that the participants make errors on nouns that are followed by averb and adjectives followed by an adverb the least. In terms of grammatical collocationalerrors, the results show that the errors on nouns followed by a preposition and verbs followedby a preposition and an object are found the most, whereas the errors on verbs followed bygerund and verbs followed by an object and infinitive are found the least. Moreover, the majorsources of collocational errors are the first language transfer, followed by ignorance of rulerestriction, overgeneralization, approximation, false concept hypothesized and synonym strategy.